PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN QUIZIZZ PADA ELEMEN KOMUNIKASI DI TEMPAT KERJA TERHADAP HASIL BELAJAR SISWA KELAS XI MANAJEMEN PERKANTORAN DI SMKS RAJASA SURABAYA - Citra Arianti, Amelia; Puspasari, Durinta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the effect of the Quizizz-assisted Problem Based Learning (PBL) model on the learning outcomes of Grade XI Office Management students in the Workplace Communication element at SMKS Rajasa Surabaya. A quantitative approach was applied using a quasi-experimental method with a nonequivalent control group design, involving an experimental class taught with PBL assisted by Quizizz and a control class receiving conventional instruction. Data were gathered through pretest and posttest and processed with normality, homogeneity, Independent Samples t-test, and N-Gain analyses using IBM SPSS Statistics version 27. The results showed a significance value (Sig. 2-tailed) of 0.043 (< 0.05), so the null hypothesis was rejected and the alternative hypothesis accepted. The average N-Gain score reached 57.81% for the experimental class and 53.77% for the control class. It can therefore be concluded that the Quizizz-assisted PBL model has a significant effect on students' learning outcomes in the Workplace Communication element.